La difficile transparence des statistiques épidémiologiques de la COVID-19 ou comment les minorités peinent à exister dans la bataille des chiffres en Amazonie - Stoll, Emilie; Alencar, Edna; Benitz, Tabatha; Mota Cardoso, Thiago; Dias Flores, Luiza; Capredon, Élise; Folhes, Ricardo; Soares de Cortes, João Paulo; Tupiassu, Lise; Fischer, Luly; Priam, Jonathan (Anthropologica, 2022)
In Amazonas, one of the regions of Brazil most affected by the COVID‑19 epidemic, epidemiological statistics published by authorities paint a picture of the health crisis that must be called into question, as it does not or only partially considers the situation of ethnic and cultural minorities living in the region. During the first wave of the pandemic (from February to July 2020), a team of 11 researchers documented and analyzed the protests of Indigenous populations and quilombolas and their appropriation of statistical tools, to appear in the official statistics. As a response to these protests, epidemiological updates published by the states and Amazonian municipalities evolved greatly from one month to the next, reflecting the different interpretations of the health crisis anchored in the imaginations and power interests of Amazonian regions. The analysis underscores the subtle but essential fight of the country’s ethnic minorities to ensure that the consequences of the epidemic on their population are recorded both in the official numbers and in policies.